Structural investigations of lipids and proteins using MS ultraviolet photodissociation - Sommer, Simon; Justus Liebig University Giessen (My University, 2022)
Ultraviolet photodissociation (UVPD) is an emerging method for the structural analysis of molecular ions in mass spectrometric experiments. To increase the capabilities of UVPD in bioanalytical research, new structure-specific workflows are required and details of the UVPD-triggered fragmentation event need to be understood to improve the scope of the methodology. In the presented work, UVPD methods were developed and used to tackle existing challenges of analyte characterization in lipidomics and proteomics. In particular, an UVPD workflow for the discrimination of sn-isomers was developed. Bivalent metal salts (e.g., FeCl2) were added to electrospray ionization (ESI) solvents. This led to the formation of doubly charged metal-glycerophospholipid (GP) ions, which were fragmented using collision-induced dissociation and UVPD. Selective cleavage of the fatty acid in sn-2 position was observed. The selectivity of the fragmentation was used as a measure for the relative sn-isomer abundance in egg yolk, porcine brain, yeast, and mouse pancreas lipid extracts. In order to rationalize the sn-selectivity introduced via metal ion-adduction, the structures of precursor and fragment ions were investigated. Infrared multiphoton dissociation (IRMPD) spectra of [GP + H/Na/K/Fe]+/2+ and [GP + Na/K - 183]+ were obtained. By comparison of the IRPMD spectra to theoretical spectra of quantum-chemically predicted structures, gas-phase structures of the precursor and fragment ions were assigned. The gas-phase structures of the precursor and the fragment were used to draw conclusions of likely fragmentation mechanism of GP ions. Lastly, the fragmentation sites and efficiencies of intact protein ions upon UVPD activation as a function of the charge carrier quantity and position were investigated. The model proteins ubiquitin, cytochrome c, and myoglobin were sprayed from ESI solutions containing substances for native, denaturing, and supercharging of the proteins. Comparison of the data with calculations of charge carrier positions revealed a correlation between the location of the charge carrier and the fragmentation sites.
Keywords: Mass Spectrometry; UVPD; Lipid; Protein; ddc:540